Research of oxidative stress participation in the development of the radiation-induced bystander effect in human peripheral blood lymphocytes - Shemetun, O.V.; Talan, O. O. (Reports of the National Academy of Sciences of Ukraine, 2014)
The radiation-induced bystander effect is modeled with the help of a mixed cell culture consisting of peripheral blood lymphocytes obtained from individuals of different sexes irradiated in vitro in a dose of 1 Gy and unirradiated. The frequency of chromosome aberrations in unirradiated bystander-cells without and under the action of an antioxidant vitaminic medical product had been determined. It had been found that the impact of the antioxidant into the mixed culture before the cultivation prevented the occurrence of the radiation-induced bystander effect. The data obtained testify to the participation of oxidative stress in the mechanism of bystander effect development.